2008
DOI: 10.1143/jpsjs.77sa.61
|View full text |Cite
|
Sign up to set email alerts
|

Universal Relation between Guest Free Space and Lattice Thermal Conductivity Reduction by Anharmonic Rattling in Type-I Clathrates

Abstract: Since the early days of studies on thermoelectric clathrates it has been evidenced that the lowering of thermal conductivity in these compounds is related to the guest ion's rattling characteristics. Here we report on the relation between the guest vibration and lattice thermal conductivity κL in single crystalline samples of type-I clathrates Ba8In16Ge30−xMx (M = Si, Sn) with n-type carriers. On going from Mx = Si1.6 to Mx = Sn2.2, the lattice parameter increases by 1% from 11.20 to 11.30Å. This is accompanie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
2
16
0
1
Order By: Relevance
“…We also note that the guest off‐center motion is the primary factor responsible for the suppression of thermal conductivity 22, 17. It was revealed in Ref.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…We also note that the guest off‐center motion is the primary factor responsible for the suppression of thermal conductivity 22, 17. It was revealed in Ref.…”
Section: Resultssupporting
confidence: 54%
“…High atomic weight in the framework can reduce the speed of sound in the material, and thereby decrease the thermal conductivity. At the same time, the studies indicated that the cage size increases as the majority cage atom changes from Si, Ge to Sn, which leads to the decrease of thermal conductivity [17]. It is also noteworthy that the lattice conductivity k L within each of these three series decreases with the decrease of the guest ionic radius r guest from Cs 1þ , Rb 1þ , Ba 2þ , Sr 2þ , to Eu 2þ [18,19].…”
mentioning
confidence: 99%
“…High atomic weight in the framework can reduce the speed of sound in the material, and thereby decrease the thermal conductivity. At the same time, the studies indicated that the cage size increases as the majority cage atom changes from Si, Ge to Sn, which leads to the decrease of thermal conductivity 17. It is also noteworthy that the lattice conductivity κ L within each of these three series decreases with the decrease of the guest ionic radius r guest from Cs 1+ , Rb 1+ , Ba 2+ , Sr 2+ , to Eu 2+ 18, 19.…”
Section: Introductionmentioning
confidence: 88%
“…Suekuni et al studied the relationship between the lattice thermal conductivity of various Type I inorganic clathrates as a function of the cage radius and suggested that lattice thermal conductivity values scale well with the free space available for the guest ion in the cage. 83 Therefore, by appropriately choosing the guest and framework elements, the lattice thermal conductivity can be further tuned.…”
Section: Esr Identifi Cation and Quantitative Analysis Of Paramagnetimentioning
confidence: 99%